Fly ash-based glass microbeads with high solar reflectance and preparation method and application thereof

CN122958883APending Publication Date: 2026-10-23WUHAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611072672.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-20
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

但粉煤灰空心微珠直接使用白度低,不适用于浅色材料的填充,并且辐射制冷效果也有限,因此需要对其进行改性

Benefits of technology

[0019]本发明的有益效果在于:1、本发明提供的粉煤灰基玻璃微珠白度高,对太阳光具有高反射率,导热系数低,具有优异的辐射制冷性能,作为填料在需要辐射制冷的涂料等产品方面具有良好的市场应用前景。2、本发明的制备方法反应条件温和,原料普通易得,易于产业化生产。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses fly ash-based glass microbeads with high solar reflectivity and a preparation method and application thereof, and the fly ash-based glass microbeads take fly ash glass microbeads with a hollow structure as a core, and are sequentially coated with a dense silicon dioxide layer and a calcium carbonate layer from inside to outside. The fly ash-based glass microbeads provided by the application have high whiteness, high solar reflectivity, low thermal conductivity and excellent radiation refrigeration performance, and have good market application prospects as fillers in products, such as coatings, which need radiation refrigeration.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of solid waste treatment technology, specifically relating to a fly ash-based glass microsphere with high solar reflectivity, its preparation method, and its application. Background Technology

[0002] Fly ash is a solid waste produced by burning pulverized coal in coal-fired power plants. my country's annual fly ash emissions are about 180 million tons. Large amounts of fly ash are piled up in ash dumps, encroaching on land resources and causing harm such as water pollution, air pollution, and human health hazards.

[0003] Glass microspheres purified from fly ash are over 90% spherical particles with low density, good dispersibility and flowability, and are non-toxic. When used as fillers, they do not cause internal stress defects, making them advantageous for use as fillers in polymers or concrete due to their abundant and readily available raw materials and low cost. Fly ash glass microspheres also possess certain thermal radiation effects, showing potential in the preparation of radiative cooling materials such as coatings, roll materials, or films. However, the direct use of hollow fly ash microspheres results in low whiteness, making them unsuitable for filling light-colored materials, and their radiative cooling effect is also limited. Therefore, modification is necessary. Existing modification methods typically involve simple inorganic coating of the fly ash glass microsphere surface. However, the coating layer is prone to peeling off and fails to achieve the synergistic optimization effect of high whiteness and high reflectivity, thus limiting the high-value applications of fly ash glass microspheres. Summary of the Invention

[0004] The technical problem to be solved by the present invention is to address the above-mentioned deficiencies in the prior art by providing a fly ash-based glass microsphere with high solar reflectivity, its preparation method and application. First, a dense silica layer is coated on the surface of the fly ash glass microsphere, and then a calcium carbonate layer is coated on it. The resulting fly ash-based glass microsphere has high whiteness and excellent thermal resistance and solar reflectivity. It can be used as a functional filler in passive radiative heat dissipation materials, such as coatings, rolls, and films, with outstanding radiative cooling effect and excellent comprehensive performance.

[0005] The first aspect of the present invention is to provide a fly ash-based glass microsphere with high solar reflectivity, which has a hollow fly ash glass microsphere as the core and is coated with a dense silica layer and a calcium carbonate layer from the inside to the outside.

[0006] According to the above scheme, the particle size of the fly ash glass microspheres is 120~180μm.

[0007] A second aspect of this invention is to provide a method for preparing the above-mentioned fly ash-based glass microspheres with high solar reflectivity, the specific steps of which are as follows: 1) Mix ammonium bisulfate solution with fly ash glass microspheres, add sodium lignosulfonate solution and sodium alginate solution, and place the resulting mixture in an ultrasonic water bath. While undergoing ultrasonic treatment in the water bath, activate the mixture by low-temperature heating. After activation, separate the solid and liquid phases using vacuum filtration, collect the filter cake to obtain activated fly ash glass microspheres, add water glass to the activated fly ash glass microspheres, and stir thoroughly to ensure the water glass is evenly dispersed on the surface of the activated fly ash glass microspheres. Then, add oxalic acid solution to adjust the pH of the system to 6-7, and continue stirring for 30-90 minutes. During this process, oxalic acid provides H₂... + Sodium silicate in water glass undergoes acidification, hydrolysis, and condensation reactions. The generated silicic acid gradually condenses to form silica, which is then deposited in situ on the surface of fly ash glass microspheres under electrostatic adsorption and self-assembly, forming a uniform and dense silica coating layer. After the reaction, solid-liquid separation is performed by vacuum filtration, and the filter cake is collected to obtain fly ash glass microspheres with a dense silica coating layer. 2) Add the fly ash glass microspheres coated with a dense silica layer obtained in step 1) and calcium carbonate powder to water, and introduce sufficient CO2 into the liquid until the liquid becomes clear. At the same time, stir slowly and adjust the pH value of the system to 7.5~8.5, then filter. Heat treat the filtered fly ash glass microspheres with the surface coating to improve the bonding stability of the silica layer and the calcium carbonate layer and the density of the coating layer. Then, let it cool naturally and dry to obtain fly ash-based glass microspheres coated with silica layer and calcium carbonate layer in sequence.

[0008] According to the above scheme, the concentration of ammonium bisulfate solution in step 1) is 5~15wt%, and the mass ratio of fly ash glass microspheres to ammonium bisulfate solution is 30~50:1.

[0009] According to the above scheme, the concentration of sodium lignosulfonate solution in step 1) is 0.2~0.6wt%, the concentration of sodium alginate solution is 0.1~0.4wt%, and the mass ratio of fly ash glass microspheres, sodium lignosulfonate solution and sodium alginate solution is 100~500:1:1~2.

[0010] According to the above scheme, in step 1), activation treatment is carried out at low temperature while performing water bath ultrasonic treatment. The specific process conditions are as follows: water bath ultrasonic treatment is performed using ultrasound with a frequency of 35~45kHz, and the temperature is raised from room temperature to 50~60℃ at a heating rate of 5~8℃ / min. After water bath ultrasonic treatment for 5~8min, it is stopped, and then stirring is continued at a stirring rate of 100~150r / min for 10~30min.

[0011] According to the above scheme, the concentration of water glass in step 1) is 10~12wt%, and the mass ratio of activated fly ash glass microspheres to water glass is 3.75~10:1.

[0012] According to the above scheme, the concentration of the oxalic acid solution in step 1) is 3~8wt%.

[0013] According to the above scheme, the stirring rate of step 1) of the stirring reaction is 100~150 r / min.

[0014] According to the above scheme, the calcium carbonate powder in step 2) has a particle size of 800~1250 mesh, and the mass ratio of fly ash glass microspheres coated with a dense silica layer, calcium carbonate powder and water is 2~5:1:10~30.

[0015] According to the above scheme, in step 2), the stirring speed is 250~300 r / min and the stirring time is 20~60 min.

[0016] According to the above scheme, the heat treatment process conditions for step 2) are: heating to 300~400℃ at a heating rate of 10~15℃ / min and holding for 30~60min.

[0017] The third aspect of the present invention includes the application of the above-mentioned fly ash-based glass microspheres with high solar reflectivity as functional fillers in passive radiative heat dissipation materials (such as coatings, rolls, films, etc.).

[0018] This invention uses hollow fly ash glass microspheres as the core, coated with a dense silica layer and a calcium carbonate layer sequentially from the inside out. The calcium carbonate layer coating the surface of the hollow glass microspheres, with its extremely high infrared emissivity in the 8-13 μm atmospheric infrared window, significantly enhances the radiative cooling effect of the glass microspheres. However, direct adhesion of calcium carbonate to the glass microspheres can easily lead to detachment and uneven coating. Therefore, this invention employs a series of improved methods, first activating the glass microspheres with ammonium bisulfate, sodium lignosulfonate, and sodium alginate. The ammonium bisulfate ionizes to release H₂... + The process removes carbon powder and metallic impurities from the surface of glass microspheres, exposing a large number of Si-OH active hydroxyl sites. Sodium lignosulfonate and sodium alginate, as anionic compound surfactants and dispersants, allow the glass microspheres to be better dispersed in aqueous solution without agglomeration, ensuring a complete reaction. Water glass dissolves and dissociates in water, and oxalic acid provides H+. +Sodium silicate is slowly neutralized, and the pH value is controlled to be weakly acidic (6-7). Silicate ions gradually hydrolyze to generate monosilicic acid and sodium oxalate. Monosilicic acid loses water molecules to generate silica, which adheres to the surface of glass microspheres. In addition, the ammonium bisulfate initially adds a positive charge to the surface of glass microspheres, and after the addition of water glass, the silica ions become negatively charged. The two have an electrostatic adsorption effect. At the same time, the generated silica spontaneously and directionally coats the surface of glass microspheres, forming self-assembled capsules. Based on the above electrostatic adsorption and self-assembly effects, the silica layer prepared by this invention has the characteristics of uniformity and density. It can fill the pits of carbon impurities on the surface of fly ash microspheres, greatly improve the whiteness of the substrate, and at the same time act as an "anchoring transition layer" to solve the problems of easy detachment and uneven coating of calcium carbonate directly attached to microspheres. In addition, the silica layer combined with the hollow cavity of hollow microspheres forms a multi-layer air insulation barrier, which greatly improves the thermal resistance and realizes the dual functions of heat preservation and cooling of the final product, greatly improving the radiation cooling performance of the product.

[0019] The beneficial effects of this invention are as follows: 1. The fly ash-based glass microspheres provided by this invention have high whiteness, high reflectivity to sunlight, low thermal conductivity, and excellent radiative cooling performance, making them promising market applications as fillers in products such as coatings that require radiative cooling. 2. The preparation method of this invention uses mild reaction conditions, readily available and common raw materials, and is easy to industrialize. Detailed Implementation

[0020] To enable those skilled in the art to better understand the technical solution of the present invention, the present invention will be further described in detail below with reference to embodiments.

[0021] The fly ash glass microspheres used in the embodiments and comparative examples of the present invention have a particle size of 120~180μm, and the calcium carbonate powder used has a particle size of 800~1250 mesh.

[0022] In the embodiments and comparative examples of this invention, "parts" refers to parts by mass.

[0023] Example 1 The specific steps of the preparation method for a fly ash-based glass microsphere with high solar reflectivity are as follows: 1) Mix 0.1 parts of ammonium bisulfate solution (10 wt%) with 4 parts of fly ash glass microspheres in a container, add 0.01 parts of sodium lignosulfonate solution (0.4 wt%) and 0.02 parts of sodium alginate solution (0.2 wt%), and place the resulting mixture in a 40 kHz ultrasonic bath for ultrasonic treatment. Simultaneously, heat the mixture from room temperature to 50 ℃ at a heating rate of 5 ℃ / min, and ultrasonically treat for 7 min. Then stir at a stirring rate of 130 r / min for 20 min, and perform solid-liquid separation by vacuum filtration. The filter cake was collected to obtain activated fly ash glass microspheres. 0.5 parts of water glass (concentration of 10%) were added to the activated fly ash glass microspheres and stirred thoroughly to make the water glass evenly cover the surface of the activated fly ash glass microspheres. Then, 0.02 parts of oxalic acid solution (mass fraction of 3%) was added to adjust the pH value of the system to 7. The reaction was continued to be stirred at a stirring rate of 120 r / min for 60 min. After the reaction was completed, solid-liquid separation was performed by vacuum filtration, and the filter cake was collected to obtain fly ash glass microspheres coated with a dense silica layer. 2) Add 3 parts of the dense silica-coated fly ash glass microspheres obtained in step 1) and 1 part of calcium carbonate powder to 20 parts of deionized water. Pass sufficient CO2 into the liquid until the liquid is clear. At the same time, stir slowly at a stirring rate of 250 r / min for 30 min. Adjust the pH of the solution to 8.5 with saturated calcium hydroxide solution and then filter. Heat the filtered fly ash glass microspheres with the surface coating to 300℃ at a heating rate of 10℃ / min and hold for 30 min. After natural cooling, dry them in a drying oven at 60℃ for 24 h. Use an ultrasonic vibrating sieve to vibrate and sieve the dried fly ash glass microspheres. The ultrasonic vibration frequency is 40 kHz and the vibration is 10 min. Then, use 80 mesh, 100 mesh and 120 mesh sieves to classify and sieve them to obtain fly ash-based glass microspheres coated with silica layer and calcium carbonate layer respectively.

[0024] Example 2 The specific steps of the preparation method for a fly ash-based glass microsphere with high solar reflectivity are as follows: 1) Mix 0.1 parts of ammonium bisulfate solution (10 wt%) with 4 parts of fly ash glass microspheres in a container. Add 0.02 parts of sodium lignosulfonate solution (0.3 wt%) and 0.03 parts of sodium alginate solution (0.2 wt%). Place the resulting mixture in an ultrasonic bath at a frequency of 35 kHz for ultrasonic treatment, while simultaneously raising the temperature from room temperature to 55 ℃ at a rate of 6 ℃ / min. Ultrasonic treatment lasts for 8 min, followed by stirring at a stirring rate of 110 r / min for 25 min. Solid-liquid separation is then performed using vacuum filtration. The filter cake was collected to obtain activated fly ash glass microspheres. 0.6 parts of water glass (concentration of 10 wt%) were added to the activated fly ash glass microspheres and stirred thoroughly to make the water glass evenly cover the surface of the activated fly ash glass microspheres. Then, 0.025 parts of oxalic acid solution (mass fraction of 4 wt%) was added to adjust the pH value of the system to 6.5. The reaction was continued to be stirred at a stirring rate of 110 r / min for 60 min. After the reaction was completed, solid-liquid separation was performed by vacuum filtration and the filter cake was collected to obtain fly ash glass microspheres coated with a dense silica layer. 2) Add the fly ash glass microspheres coated with a dense silica layer obtained in step 1) and 1.2 parts of calcium carbonate powder to 18 parts of deionized water. Pass sufficient CO2 into the liquid until the liquid is clear, and stir at a stirring rate of 260 r / min for 25 min. Adjust the pH value of the solution to 8.0 and then filter. Heat the filtered fly ash glass microspheres with the surface coating to 300℃ at a heating rate of 10℃ / min and hold for 30 min. After natural cooling, dry them in a drying oven at 60℃ for 24 h. Use an ultrasonic vibrating sieve to vibrate and sieve the dried fly ash glass microspheres at an ultrasonic vibration frequency of 40 kHz for 10 min. Then, sieve them using 80 mesh, 100 mesh and 120 mesh standard sieves to obtain fly ash-based glass microspheres coated with silica layer and calcium carbonate layer respectively.

[0025] Example 3 The specific steps of the preparation method for a fly ash-based glass microsphere with high solar reflectivity are as follows: 1) Mix 0.11 parts of ammonium bisulfate solution (10 wt%) with 4 parts of fly ash glass microspheres in a container, add 0.03 parts of sodium lignosulfonate solution (0.4 wt%) and 0.04 parts of sodium alginate solution (0.25 wt%), and place the resulting mixture in an ultrasonic bath at a frequency of 40 kHz for ultrasonic treatment. Simultaneously, increase the temperature from room temperature to 60 ℃ at a rate of 5 ℃ / min, and ultrasonically treat for 7 min. Then stir at a stirring rate of 140 r / min for 20 min, and perform solid-liquid separation by vacuum filtration. The filter cake was collected to obtain activated fly ash glass microspheres. 0.8 parts of water glass (concentration of 10wt%) were added to the activated fly ash glass microspheres and stirred thoroughly to make the water glass evenly cover the surface of the activated fly ash glass microspheres. Then, 0.03 parts of oxalic acid solution (mass fraction of 5wt%) was added to adjust the pH value of the system to 7.0. The reaction was continued to be stirred at a stirring rate of 120r / min for 60min. After the reaction was completed, solid-liquid separation was performed by vacuum filtration, and the filter cake was collected to obtain fly ash glass microspheres coated with a dense silica layer. 2) Add 4 parts of the dense silica-coated fly ash glass microspheres obtained in step 1) and 1.5 parts of calcium carbonate powder to 20 parts of deionized water. Pass sufficient CO2 into the liquid until the liquid is clear, and stir at a stirring rate of 280 r / min for 30 min. Adjust the pH of the solution to 8.3 and then filter. Heat the filtered fly ash glass microspheres with the surface coating to 300℃ at a heating rate of 15℃ / min and hold for 35 min. After natural cooling, dry them in a drying oven at 60℃ for 24 h. Use an ultrasonic vibrating sieve to vibrate and sieve the dried fly ash glass microspheres at an ultrasonic vibration frequency of 40 kHz for 10 min. Then, sieve them using 80 mesh, 100 mesh and 120 mesh standard sieves to obtain fly ash-based glass microspheres coated with silica and calcium carbonate layers respectively.

[0026] Example 4 The specific steps of the preparation method for a fly ash-based glass microsphere with high solar reflectivity are as follows: 1) Mix 0.12 parts of ammonium bisulfate solution (10 wt%) with 4 parts of fly ash glass microspheres in a container, add 0.04 parts of sodium lignosulfonate solution (0.5 wt%) and 0.05 parts of sodium alginate solution (0.3 wt%), and place the resulting mixture in an ultrasonic bath at a frequency of 45 kHz for ultrasonic treatment. Simultaneously, increase the temperature from room temperature to 60 ℃ at a rate of 8 ℃ / min, and ultrasonically treat for 6 min. Then stir at a stirring rate of 140 r / min for 30 min, and perform solid-liquid separation by vacuum filtration. The filter cake was collected to obtain activated fly ash glass microspheres. 1.0 part of water glass (concentration of 10 wt%) was added to the activated fly ash glass microspheres and stirred thoroughly to make the water glass evenly cover the surface of the activated fly ash glass microspheres. Then, 0.04 parts of oxalic acid solution (mass fraction of 6 wt%) was added to adjust the pH of the system to 7.0. The reaction was continued to be stirred at a stirring rate of 150 r / min for 90 min. After the reaction was completed, solid-liquid separation was performed by vacuum filtration, and the filter cake was collected to obtain fly ash glass microspheres coated with a dense silica layer. 2) Add the fly ash glass microspheres coated with a dense silica layer obtained in step 1) and 2.0 parts of calcium carbonate powder to 25 parts of deionized water. Pass sufficient CO2 into the liquid until the liquid is clear, and stir at a stirring rate of 300 r / min for 40 min. Adjust the pH value of the solution to 8.5 and then filter. Heat the filtered fly ash glass microspheres with the surface coating to 300℃ at a heating rate of 15℃ / min and hold for 40 min. After natural cooling, dry them in a drying oven at 60℃ for 24 h. Use an ultrasonic vibrating sieve to vibrate and sieve the dried fly ash glass microspheres at an ultrasonic vibration frequency of 45 kHz for 10 min. Then, sieve them with 80 mesh, 100 mesh and 120 mesh standard sieves to obtain fly ash-based glass microspheres coated with silica layer and calcium carbonate layer respectively.

[0027] Comparative Example 1 A fly ash glass microsphere coated only with a calcium carbonate layer, wherein the preparation method of the calcium carbonate layer is the same as in Example 3, and the specific preparation method is as follows: Four parts of fly ash glass microspheres and 1.5 parts of calcium carbonate powder were added to 20 parts of deionized water. Sufficient CO2 was introduced under the liquid surface until the liquid became clear. The mixture was stirred at a stirring rate of 280 r / min for 30 min. After adjusting the pH value of the solution to 8.3, it was filtered. The fly ash glass microspheres with the surface coating were heat-treated by heating to 300℃ at a heating rate of 15℃ / min and holding for 35 min. After cooling, they were placed in a drying oven at 60℃ for 24 h. The dried fly ash glass microspheres were then vibrated and sieved using an ultrasonic vibrating sieve at a frequency of 40 kHz for 10 min. Subsequently, they were sieved using 80 mesh, 100 mesh, and 120 mesh standard sieves to obtain fly ash glass microspheres coated only with a calcium carbonate layer.

[0028] Comparative Example 2 Unmodified fly ash glass microsphere raw material.

[0029] Performance tests were conducted on the fly ash-based glass microspheres of Examples 1-4 and Comparative Examples 1-2. Specifically, the whiteness of the samples was tested using a whiteness meter; the solar reflectance was tested using a UV-Vis-NIR spectrophotometer; the hemispherical emissivity was tested using a Fourier transform infrared spectrometer (FTIR) equipped with an integrating sphere; the thermal conductivity was tested using a thermal conductivity meter; the bulk density was determined using the graduated cylinder method; the buoyancy was determined using a buoyancy test method; and the refractoriness was determined using a refractoriness tester. Each group of samples was tested in triplicate, and the average value was taken as the final test result. The test results are shown in Table 1.

[0030] Table 1

[0031] Comparing the test results of Examples 1-4 with those of Comparative Examples 1-2, it was found that the whiteness, solar reflectance, and hemispherical emissivity of the fly ash glass microspheres obtained by surface modification in Examples 1-4 were significantly higher than those of the untreated fly ash glass microspheres (Comparative Example 2). This proves that the silica and calcium carbonate layers coating the surface of the fly ash glass microspheres have a significant effect on improving whiteness, solar reflectance, and hemispherical emissivity. At the same time, compared with fly ash glass microspheres with only a calcium carbonate layer on the surface (Comparative Example 1), fly ash glass microspheres with a silica layer in the middle (Example 3) showed a greater improvement in whiteness, solar reflectance, and hemispherical emissivity, and the floating rate increased while the thermal conductivity decreased significantly, suggesting that the silica layer has a dense structure.

[0032] The fly ash-based glass microspheres with high solar reflectivity prepared in this embodiment of the invention use hollow spheres as the matrix, with a silica layer and a calcium carbonate layer sequentially coated on the surface. The spherical matrix reduces heat conduction by utilizing diffuse reflection and hollow insulation, while the coating layer achieves efficient solar reflection by matching particle size and high refractive index, suppressing daytime heat absorption. At the same time, the dense coating structure can reduce particle agglomeration and improve interfacial bonding stability, giving the material excellent radiative cooling performance. It can be applied in industries such as coatings, building materials, plastics, and rubber, reducing the occurrence of fires and ensuring the safety of people's lives and property.

[0033] It should be understood that those skilled in the art can make improvements or modifications based on the above description, and all such improvements and modifications should fall within the protection scope of the appended claims.

Claims

1. A fly ash-based glass microsphere with high solar reflectivity, characterized in that, It uses hollow fly ash glass microspheres as its core, and is coated with a dense silica layer and a calcium carbonate layer from the inside out.

2. The fly ash-based glass microspheres with high solar reflectivity according to claim 1, characterized in that, The fly ash glass microspheres have a particle size of 120~180μm.

3. A method for preparing fly ash-based glass microspheres with high solar reflectivity as described in claim 1 or 2, characterized in that, The specific steps are as follows: 1) Mix ammonium bisulfate solution with fly ash glass microspheres, add sodium lignosulfonate solution and sodium alginate solution, and activate the mixture by ultrasonic treatment in a water bath and low-temperature heating. After activation, separate the solid and liquid phases to obtain activated fly ash glass microspheres. Add water glass to the activated fly ash glass microspheres and stir thoroughly to ensure the water glass is evenly dispersed on the surface of the activated fly ash glass microspheres. Then add oxalic acid solution to adjust the pH of the system to 6-7, and continue stirring for 30-90 minutes. During this process, oxalic acid provides H₂. + Sodium silicate in water glass undergoes acidification, hydrolysis, and condensation reactions. The generated silicic acid gradually condenses to form silica, which is then deposited in situ on the surface of fly ash glass microspheres under electrostatic adsorption and self-assembly, forming a uniform and dense silica coating layer. After the reaction is completed, solid and liquid are separated to obtain fly ash glass microspheres with a dense silica coating layer. 2) Add the fly ash glass microspheres coated with a dense silica layer obtained in step 1) and calcium carbonate powder to water, and introduce sufficient CO2 into the liquid until the liquid becomes clear. At the same time, stir slowly and adjust the pH value of the system to 7.5~8.5, then filter. Heat treat the fly ash glass microspheres with the surface coating, then let them cool naturally and dry to obtain fly ash-based glass microspheres coated with silica and calcium carbonate layers in sequence.

4. The method for preparing fly ash-based glass microspheres with high solar reflectivity according to claim 3, characterized in that, Step 1) The concentration of the ammonium bisulfate solution is 5~15wt%, and the mass ratio of the fly ash glass microspheres to the ammonium bisulfate solution is 30~50:

1.

5. The method for preparing fly ash-based glass microspheres with high solar reflectivity according to claim 3, characterized in that, Step 1) The concentration of the sodium lignosulfonate solution is 0.2~0.6wt%, the concentration of the sodium alginate solution is 0.1~0.4wt%, and the mass ratio of the fly ash glass microspheres, sodium lignosulfonate solution and sodium alginate solution is 100~500:1:1~2.

6. The method for preparing fly ash-based glass microspheres with high solar reflectivity according to claim 3, characterized in that, Step 1) The obtained mixture is subjected to water bath ultrasonic treatment and low-temperature heating activation treatment. The specific process conditions are as follows: water bath ultrasonic treatment is performed with an ultrasonic frequency of 35~45kHz, and the temperature is increased from room temperature to 50~60℃ at a heating rate of 5~8℃ / min. After water bath ultrasonic treatment for 5~8min, it is stopped, and then stirring is continued at a stirring rate of 100~150r / min for 10~30min.

7. The method for preparing fly ash-based glass microspheres with high solar reflectivity according to claim 3, characterized in that, In step 1), the concentration of water glass is 10-12 wt%, and the mass ratio of activated fly ash glass microspheres to water glass is 3.75-10:1; in step 1), the concentration of oxalic acid solution is 3-8 wt%; and in step 1), the stirring rate of the stirring reaction is 100-150 r / min.

8. The method for preparing fly ash-based glass microspheres with high solar reflectivity according to claim 3, characterized in that, Step 2) The calcium carbonate powder has a particle size of 800~1250 mesh, and the mass ratio of fly ash glass microspheres coated with a dense silica layer, calcium carbonate powder and water is 2~5:1:10~30; Step 2) The stirring speed of slow stirring is 250~300 r / min, and the stirring time is 20~60 min.

9. The method for preparing fly ash-based glass microspheres with high solar reflectivity according to claim 3, characterized in that, Step 2) The heat treatment process conditions are as follows: heat to 300-400℃ at a heating rate of 10-15℃ / min, and hold for 30-60min.

10. The application of fly ash-based glass microspheres with high solar reflectivity as a functional filler in passive radiative heat dissipation materials, as described in claim 1 or 2.